EMPOWERMENT OF MENTALLY RETARDED CHILDREN THROUGH MAKING HYDROPONIC MINI PARKS IN EXCEPTIONAL ELEMENTARY SCHOOL B / C DHARMA WANITA PERSATUAN PROVINCE OF SOUTH KALIMANTAN - Giyarto Nugroho; Robby Rahmadi; Habibah Nurhayati; Nasidawati Nasidawati; Tinah Tinah (Bernas : Jurnal Penelitian Pertanian, 2019)
Children intellectual barriers have a lower IQ than normal children who have an impact on thinking skills so that intellectual obstacle education is more directed to skills education. This empowerment takes place in Exceptional Elementary School B / C Dharma Wanita Persatuan of South Kalimantan Province. The purpose of this research is (1) To provide education to the children’s tunagrahita about the importance of improving the quality of soft skill through cultivation and entrepreneurship activities. (2) Train and empower children with tunagrahita make mini hydroponic park. (3) Obtaining by conducting cultivation of plants through mini garden of entrepreneurial hydroponics that is easy and profitable. (4) To open the society’s insight on the competence of the child’s tunagrahita so that the increased social support about its existence. Mantra Nini program is done by education method of planting of mustard seeds, drying of mustard seeds, transferring of mustard seedlings into the hydroponic framework, the treatment of mustard seeds, harvesting of mustard to children with disabilities. The results obtained indicate the existence of hydroponic skills in child tunagrahita through skill learning activities by applying hydroponic axis system. Prepare tools and materials (Very good), punch rockwool (enough), put seeds into rockwol (good), wet rockwool (good), transfer seeds in net pot (very good), put net pot in hydroponic framework (excellent), replenishment of nutrients into water containers (less).